An Analysis of Covid-19 Transmission in Indonesia and Saudi Arabia - Meksianis Z. Ndii; Panji Hadisoemarto; Dwi Agustian; Asep K. Supriatna (Communication in Biomathematical Sciences, 2020)
An outbreak of novel coronavirus has been happening in more than 200 countries and has shocked society. Several measures have been implemented to slowing down the epidemics while waiting for vaccine and pharmaceutical intervention. Using a deterministic and stochastic model, we assess the effectiveness of current strategies: reducing the transmission rate and speeding up the time to detect infected individuals. The reproductive ratio and the probability of extinction are determined. We found that the combination of both strategies is effective to slow down the epidemics. We also find that speeding up the time to detect infected individuals without reducing the transmission rate is not sufficient to slow down the epidemics.